Pelaksanaan Al-Qarḍ Al-Ḥasan Dalam Agihan Zakat Terhadap Asnaf al-Ghārimīn di Institusi-Institusi Zakat di Malaysia - Ismail, Halim; Daud, Mohd Noor (UPSI TANJONG MALIM, 2018)
The study aims to describe the implementation of al-Qarḍ al-Ḥasan in the distribution of zakat to asnaf al-Ghārimīn in the institutions of zakat in Malaysia. This study uses qualitative methods and analyzes using inductive, deductive and comparative methods. Studies show that there are zakat institutions in Malaysia that carry out the zakat distribution on asnaf al-Ghārimīn in al-Qarḍ al-Ḥasan as well as states which provide zakat distribution rules to asnaf al-Ghārimīn in the form of al-Qarḍ al-Ḥasan. However, the amount of zakat distribution of asnaf al-Ghārimīn by zakat institutions in Malaysia is still low. This study implies the implementation of zakat distribution on asnaf al-Ghārimīn by al-Qarḍ al-Ḥasan in order to resolve the current issues of the asnaf.